2012
DOI: 10.3390/ijms131114401
|View full text |Cite
|
Sign up to set email alerts
|

Changes on the Caco-2 Secretome through Differentiation Analyzed by 2-D Differential In-Gel Electrophoresis (DIGE)

Abstract: Colorectal cancer is still a major health burden worldwide, and its diagnosis has not improved in recent years due to a lack of appropriate diagnostic serum markers. Aiming to find new diagnostic proteins, we applied the proteomic DIGE technology to analyze changes in the secretome before/after differentiation of the colon adenocarcinoma Caco-2 cell line, an accepted in vitro model to study colorectal tumorigenesis. When the secretomes from undifferentiated (tumor-like) and differentiated cells (resembling hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…The differentiation stage of the epithelial cells affects the expression of surface molecules (30,31), which affects the bacterial adhesion to the cells (32). In accordance, our results show various levels of adhesion to the epithelial cells of different ages or at different stages of differentiation.…”
Section: Discussionsupporting
confidence: 78%
“…The differentiation stage of the epithelial cells affects the expression of surface molecules (30,31), which affects the bacterial adhesion to the cells (32). In accordance, our results show various levels of adhesion to the epithelial cells of different ages or at different stages of differentiation.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the enterocyte binding strength of A. muciniphila was independent of the growth state of Caco-2 cells, indicating that the host-binding site utilized by the bacterium is expressed on the cell surface irrespective of the state of cell differentiation. It is well known that the expression of surface molecules is influenced by the differentiation stage in epithelial cells (28,29) and that bacterial adhesion to enterocytes is affected by the profile of surface-associated molecules in the enterocytes (30). Based on our findings, it seems possible that A. muciniphila is able to bind enterocytes at various differentiation stages in vivo.…”
Section: Discussionmentioning
confidence: 71%
“…In vitro cell models play an important role in understanding cellular related to up normal human physiological conditions. García-Lorenzo et al [ 28 ] reported an upregulation in non-differentiated Caco-2 cells, especially, in proteins involved in cell growth and proliferation related to cancer, confirming the tumoral phenotype of these cells. To that end, investigating the anti-cancer effect of L. acidophilus was performed with verification of the probable effect of its polysaccharides extract on the inhibition of colon cancer cell proliferation (87.27%) and cell death (80.65%) with 1.96–51.3 colon cancer selectivity index.…”
Section: Discussionmentioning
confidence: 86%